2011
DOI: 10.1016/j.neuroimage.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical fMRI: Evidence for a 7T benefit over 3T

Abstract: Despite there being an increasing number of installations of ultra high field MR systems (> 3 T) in clinical environments, no functional patient investigations have yet examined possible benefits for functional diagnostics. Here we performed presurgical localization of the primary motor hand area on 3 T and 7 T Siemens scanners with identical investigational procedures and comparable system specific sequence optimizations. Results from 17 patients showed significantly higher functional sensitivity of the 7 T s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
113
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 28 publications
(29 reference statements)
4
113
0
1
Order By: Relevance
“…Some early studies at 7 T could confirm the enhanced SNR during motor tasks [58]. Even single block analyses at 7 T revealed similar or even higher response strength than multi-block measurements at 1.5 T or 3 T. Since those first results, many studies have confirmed the high impact for clinical fMRI at ultra-high field systems [59]. Exact mapping of the somatosensory cortex has been demonstrated at 7 T fMRI leading to the possibility of more dedicated clinical evaluation, for example, pre-surgically [60].…”
Section: Clinical Fmrimentioning
confidence: 93%
“…Some early studies at 7 T could confirm the enhanced SNR during motor tasks [58]. Even single block analyses at 7 T revealed similar or even higher response strength than multi-block measurements at 1.5 T or 3 T. Since those first results, many studies have confirmed the high impact for clinical fMRI at ultra-high field systems [59]. Exact mapping of the somatosensory cortex has been demonstrated at 7 T fMRI leading to the possibility of more dedicated clinical evaluation, for example, pre-surgically [60].…”
Section: Clinical Fmrimentioning
confidence: 93%
“…A first study comparing 3T and 7T motor cortex signals in patients with brain tumors provided promising results: Five of 6 functional parameters indicated improved sensitivity for 7T, even at a standard resolution (1.8 ϫ 1.8 ϫ 3 mm voxel size) and with standard clinical procedures. 4 Corresponding language data (work in progress) achieved with an overt response paradigm that includes various subcomponents of language processing 5 indicate a similar 7T benefit, provided that the artifacts situation can be controlled (Fig 1).…”
mentioning
confidence: 89%
“…Improved functional signal strength in a patient with tumor generated by a 7T (Siemens Magnetom) ultra-high-field system within the Wernicke language area (overt speech design, Study Group Clinical fMRI 4 ).…”
mentioning
confidence: 99%
“…6 A recent study revealed that there was a small difference in the mean cortical thickness among five healthy volunteers between 3T and 7T MRI system. 7 However, the sensitivity of structural imaging on 7T MRI has not been fully investigated.…”
mentioning
confidence: 99%
“…However, ultrahigh field strength could also be apt to produce ghosting, head motion artifacts and heterogeneous signal intensity, 6 which could affect the evaluation of subtle structures. There haven't been enough data on using 7T…”
mentioning
confidence: 99%